The challenges in making library services accessible to incarcerated male juveniles in five correctional schools - Rafedzi, E.R.K.; A., Abrizah; Yu, Halida; Rafedzi, E.R.K.; Abrizah, A.; Yu, Halida (Malaysian Journal of Library and Information Science, 2016)
This qualitative study extends our earlier research on what we have learned about the information needs of Malaysian male juvenile offenders. This study explores the extent to which the prison library is used as the environment for information seeking of male juvenile delinquents. Data were collected using participants’ observation with 27 juveniles (13 to 21 years old) living in five correctional schools in Malaysia. Our observation at all research sites has led us to conclude that the prison library does not play much role in addressing the participants’ information needs. The findings in this research are useful for the purpose of designing and delivering the best possible library services to this group. findings add to the limited literature on juvenile offenders’ information needs and how the prison libraries meet the needs of this people.